El río de Juan Rulfo (Dossier: Muertos que narran) - Villoro, Juan (2024)
The anecdote of an encounter between two consecrated writers allows us to identify certain features of Juan Rulfo’s writing and authorial figure, such as the use of a foreign perspective to perceive what is his own and the strategy of producing a masterpiece that is extremely bounded in order to avoid eventual failure. The calibrated use of foreign voices in Rulfo’s narrative gives way to the recognition of fatal responsibilities and to a speech of defeated and dead people who never cease to confess, whose bodies adjust to the drifts of a silent river.